2019
DOI: 10.3389/fevo.2019.00422
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Soil Feedbacks of Plantago lanceolata in the Field Depend on Plant Origin and Herbivory

Abstract: Soil biota involved in plant-soil feedbacks (PSFs) have an impact on the growth of plant individuals. So far, studies investigating the role of soil-biota mediated PSFs in plant performance were mostly performed in greenhouses and focused predominantly on species differences, whereas the contribution of PSFs to plant performance under field conditions and intraspecific variation in PSFs among plant populations remain poorly investigated. Here, we performed a PSF pot experiment under field conditions to study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 77 publications
(116 reference statements)
0
10
1
Order By: Relevance
“…By selectively damaging particular plant species, insect herbivores alter competitive relationships and thus codetermine species local abundances (Borgström et al 2016, Engelkes et al 2016). Though it has rarely been examined (Smith‐Ramesh and Reynolds 2017), herbivores can also differently influence individuals within a single species (Bezemer et al 2005, Heinze and Joshi 2018, Heinze et al 2019, Kirchhoff et al 2019). These studies suggest a potentially strong interaction between PSF and aboveground herbivory, though they have generally been performed in greenhouse and not in field conditions (e.g., Bezemer et al 2005, Engelkes et al 2008, Kos et al 2015; but see, e.g., Heinze and Joshi 2018, Hannula et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…By selectively damaging particular plant species, insect herbivores alter competitive relationships and thus codetermine species local abundances (Borgström et al 2016, Engelkes et al 2016). Though it has rarely been examined (Smith‐Ramesh and Reynolds 2017), herbivores can also differently influence individuals within a single species (Bezemer et al 2005, Heinze and Joshi 2018, Heinze et al 2019, Kirchhoff et al 2019). These studies suggest a potentially strong interaction between PSF and aboveground herbivory, though they have generally been performed in greenhouse and not in field conditions (e.g., Bezemer et al 2005, Engelkes et al 2008, Kos et al 2015; but see, e.g., Heinze and Joshi 2018, Hannula et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Patterns of seedling performance that fit the predictions of negative intraspecific PSFs have been demonstrated in a handful of plant species (Bukowski & Petermann, 2014;Liu et al, 2015;Bukowski et al, 2018;Eck et al, 2019;Kirchoff et al, 2019;Crawford & Hawkes, 2020), but positive intraspecific PSFs can also occur (Bukowski & Petermann, 2014), as well as lack of intraspecific PSFs in some species (Rallo et al, 2023). Furthermore, existing evidence of intraspecific PSFs arises primarily from experiments conducted under controlled conditions (but see Browne & Karubian, 2016;Kirchoff et al, 2019). In a prior shadehouse experiment, we found that seedlings of a tropical tree species (Virola surinamensis) had reduced growth in the soil microbial community from beneath their maternal tree relative to the soil microbial community from beneath non-parent conspecific trees in their population (Eck et al, 2019).…”
Section: Introductionmentioning
confidence: 76%
“…Recent experimental evidence suggests that intraspecific PSFs can occur within populations (Eck et al, 2019; Crawford & Hawkes, 2020) and among populations (Bukowski & Petermann, 2014; Liu et al, 2015; Wagg et al, 2015; Bukowski et al, 2018; Kirchoff et al, 2019) of the same plant species. Intraspecific PSFs can be characterized by variation in the performance of closely related seedlings (e.g., offspring) versus unrelated seedlings when exposed to the soil microbial communities of conspecific adults within their population.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies on the model species Arabidopsis thaliana showed that negative PSF effects depended on which accession had previously occupied the soil (Aguilera et al 2011; Bukowski and Petermann 2014). Differences in PSFs within species have been documented also in Plantago lanceolata (Kirchhoff et al 2019) and Trifolium pratense (Wagg et al 2015). However, studies have mainly focused on forbs, and the intraspeci c variation for plant-soil feedbacks in other plant taxonomic groups remain still unresolved.…”
Section: Introductionmentioning
confidence: 99%